A Content Analysis on English Textbook for Seventh Graders: When English Rings A Bell - Riska Ramadhani; Endang Komariah; Nira Erdiana (Research in English and Education Journal, 2022)
The textbook is one of the media used in English language learning. A great number of EFL textbook evaluations have been done to find the most suitable textbook for English language teaching. The present study was aimed to determine the suitability of materials in the textbook “When English Rings a Bell” with the criteria of a good English textbook by Curriculum 2013. Besides that, the researcher also studies the feasibility of content, language, and presentation aspects of the textbook. This study uses a descriptive qualitative approach. The data collected for this study will be gathered from the English textbook “When English Rings a Bell” semester 1 published by the Ministry of Education and Culture of Indonesia. The data were gathered by evaluating the textbook using the checklist containing the criteria of textbook evaluation. In the data analysis technique, the percentage of criteria fulfillment was calculated by dividing the total of criteria points that were met in a textbook for each sub aspect with the total of criteria points in each sub aspect. It was then multiplied by 100%. The result showed that the English textbook entitled “When English Rings a Bell” semester 1 for Grade VII Junior High School has fulfilled the criteria of content, language, and presentation. The result showed that “When English Rings a Bell” semester 1 for Grade VII Junior High School have fulfilled the criteria of a good textbook by achieving the average fulfillment score of 86,36% with the fulfillment of 95% for content aspect, 100% for language aspect, and 86% for presentation aspect.